2007 Topical Meeting on Silicon Monolithic Integrated Circuits in RF Systems 2007
DOI: 10.1109/smic.2007.322813
|View full text |Cite
|
Sign up to set email alerts
|

A CMOS Power Amplifier using Ground Separation Technique

Abstract: This work presents an on-chip ground separation technique for power amplifiers. The ground separation technique is based on separating the grounds of the amplifier stages on the chip and thus any parasitic feedback paths are removed. Simulation and experimental results show that the technique makes the amplifier less sensitive to bondwire inductance, and consequently improves the stability and performance.A two-stage CMOS RF power amplifier for WCDMA mobile phones is designed using the proposed on chip ground … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…A reported investigation [18] has shown that the substrate noise coupling between the power cells and transformers may affect the stability of RF power amplifiers, especially when the maximum output power of the RF power amplifier is high. To reduce the substrate noise coupling in the RF circuits, the substrate isolation techniques are reportedly employed.…”
Section: Output Stage 221mentioning
confidence: 99%
“…A reported investigation [18] has shown that the substrate noise coupling between the power cells and transformers may affect the stability of RF power amplifiers, especially when the maximum output power of the RF power amplifier is high. To reduce the substrate noise coupling in the RF circuits, the substrate isolation techniques are reportedly employed.…”
Section: Output Stage 221mentioning
confidence: 99%